Identification and Characterization of Fusolisin, the Fusobacterium nucleatum Autotransporter Serine Protease - Doron, Lior (Public Library of Science, 2014)
Fusobacterium nucleatum is an oral anaerobe associated with periodontal disease, adverse pregnancy outcomes and colorectal carcinoma. A serine endopeptidase of 61–65 kDa capable of damaging host tissue and of inactivating immune effectors was detected previously in F. nucleatum. Here we describe the identification of this serine protease, named fusolisin, in three oral F. nucleatum sub-species. Gel zymogram revealed fusobacterial proteolytic activity with molecular masses ranging from 55–101 kDa. All of the detected proteases were inhibited by the serine protease inhibitor PMSF. analysis revealed that all of the detected proteases are encoded by genes encoding an open reading frame (ORF) with a calculated mass of approximately 115 kDa. Bioinformatics analysis of the identified ORFs demonstrated that they consist of three domains characteristic of autotransporters of the type Va secretion system. Our results suggest that the F. nucleatum fusolisins are derived from a precursor of approximately 115 kDa. After crossing the cytoplasmic membrane and cleavage of the leader sequence, the C-terminal autotransporter domain of the remaining 96–113 kDa protein is embedded in the outer membrane and delivers the N-terminal S8 serine protease passenger domain to the outer cell surface. In most strains the N-terminal catalytic 55–65 kDa domain self cleaves and liberates itself from the autotransporter domain after its transfer across the outer cell membrane. In F. nucleatum ATCC 25586 this autocatalytic activity is less efficient resulting in a full length membrane-anchored serine protease. The mature serine protease was found to cleave after Thr, Gly, Ala and Leu residues at the P1 position. Growth of F. nucleatum in complex medium was inhibited when serine protease inhibitors were used. Additional experiments are needed to determine whether fusolisin might be used as a target for controlling fusobacterial infections.